The impact of territorial care in the treatment of people diagnosed with schizophrenia and delusional disorders in a Rio de Janeiro community - Joana Thiesen; Sandra Fortes; Maria Tavares Cavalcanti (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
Care for people diagnosed with schizophrenia and delusional disorders involves many challenges, especially in territorial contexts of pronounced social vulnerability. In Rio de Janeiro, the two decades after the passing of Federal Law 10,216 on Psychiatric Reform in 2001 have been characterized by the transition from a hospital-centered model to one based on community services. Taking the case of a community in Rio de Janeiro, data was extracted from the medical records of 94 patients diagnosed with schizophrenia, schizotypal disorders, and delusional disorders (ICD-10 codes F20 to F29) in five public health services. Covering the period from 2003 to 2016, indicators of the quality of treatment provided were analyzed. As a result of this transition, psychiatric hospitals have all but emptied and a low number of currently untreated patients can be observed. In addition, crisis care and long-term hospitalizations have been replaced by territorial care, and clinical comorbidities are monitored and treated at Family Health Units.